An AIE‐Active Ultrathin Polymeric Self‐Assembled Monolayer Sensor for Trace Volatile Explosive Detection. Issue 23 (17th October 2021) - Li, Mingliang; Xie, Kefeng; Wang, Guozhi; Zheng, Jing; Cao, Yingnan; Cheng, Xiang; Li, Ziwei; Wei, Feng; Tu, Hailing; Tang, Jinyao
Abstract: This work has prepared polymeric self‐assembled monolayer (SAM) sensors for the detection of trace volatile nitroaromatic compound (NAC) explosives by fluorescence quenching. A typical aggregation‐induced emission (AIE) luminogen 1, 1, 2, 2‐tetraphenylethene (TPE) polymerizes into PTPE to increase the fluorescence intensity in the SAMs, and the phosphoric acid acts as the anchor group to form stable covalent bonds with the Al2 O3 substrate. This design takes advantage of the high sensitivity and good stability of SAMs, and high fluorescence intensity, and "wire effect" of the conjugated polymers. The polymeric SAM sensors are prepared on the Al2 O3 silicon wafer and testing paper. Both of them show good response speed, reversibility, selectivity, and sensitivity. The detection limits down to 0.07, 0.35, and 4.11 ppm for TNT, DNB, and NB, respectively, are achieved on the inorganic testing paper. Furthermore, due to the higher fluorescence intensity by interlacing and overlapping of fibers, the detection of the paper can be distinguished by naked eyes even with a low‐power handheld UV lamp, which provides an experimental basis for the development of cheap and easy trace NAC explosive sensors. Abstract : Based on aggregation‐induced emission (AIE) effect, an ultra‐thin self‐assembled monolayer (SAM) sensor for trace nitro explosives is designed. The polymeric SAMs are fabricated by covalent bonds to the substrate, and proved with good stability, sensitivity, selectivity and reversibility. The sensing properties are further improved by being coated on Al2 O3 fiber paper, which realizes the detection by naked eyes.